Providing enhanced security in IoT based smart weather system - Y Narasimha Rao; P. Surya Chandra; V. Revathi; N. Suresh Kumar (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Weather reporting system consist multiple devices which are playing dynamic role in producing dynamic environmental parameters such as temperature, humidity, and air pollution. It was a tedious task to bring all the devices together and make them interleaving to produce relevant measurement. Recent trends have proven that the IoT has brought all the devices and peripherals in one place to make more flexible and smart measurement. In the traditional weather monitoring system measurement method is not real time, not continuous and also tedious job to take continuous measurement. But, the IoT has completely changed the measurement scenario and improved the consistency of the measurement. In the present work the environmental parameters such rainfall, temperature, humidity, and density of carbon dioxide in the air are measured with sensors. The Arduino Uno card gathers all information from the devices which are associated with its port pins. The information is sent to cloud server for record and future retrieving. At the same time the data security in cloud been assured with encryption and decryption data while retrieving the information from cloud. This enhances the security, ease of accessing the cloud data from mobile applications, provides wise predictions and minimizes the communication overhead.